Implementation of Islamic Morning Stories in Implementing Student's Religious Character in SD Alam Ar-Rohmah - Eka Firmansyah; Novita Asna Wardati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
This study aims to describe the implementation of Islamic morning stories at SD Alam Ar-Rohmah Malang. This research is a type of research that is used a qualitative approach with case study design, in this case by observing the implementation of Islamic morning stories on students, as well as to find out directly the morals of students. This study uses data collection techniques using interviews, observation, and documentation. The data were obtained directly from respondents regarding the implementation of Islamic morning stories. All of these data are materials to describe the implementation of the morning story at SD Alam Ar-Rohmah Malang. The results showed that the Islamic morning story by a teacher besides having the obligation to teach also has an obligation to carry out his role as an educator who prioritizes the formation and development of the affective field or attitudes and behavior of students, especially the homeroom teacher who is the spearhead in fostering the morals of students in the classroom in elementary school. This is because at this age is a fundamental period that must be given a foundation of moral values. In the moral development of students, it is not uncommon for obstacles related to moral problems to occur in students. Therefore, the role of a teacher becomes the main solution in fostering the morals of students. The purpose of this study is to investigate the implementation of Islamic morning stories on students in fostering children's morals.